Improvement of Teachers' Ability in Creating Modules with Information Technology on Vocational High Schools West Sumatera - Hasan maksum; Martias Martias; Wawan Purwanto; Ahmad Arif (AEEJ : Journal of Automotive Engineering and Vocational Education, 2025)
The purpose of this analysis was to look at the teacher's ability to improve the teacher's ability to develop online-based teaching materials. The transition period between the pandemic and after requires strategies to ensure that the learning transition continues to provide students with comfort in their learning. The activity drew 30 people, all of whom were members of the West Sumatra Automotive Engineering Subject Teacher Consultation. They are divided into two categories: online and offline. The online module work created by the participants will be analyzed to determine the effectiveness of the learning and the teacher's ability to create online modules. As a result, participants can create effective learning modules. However, it takes longer for the presenters to teach those who are online how to complete the task.